ALTERNATIF PENYELESAIAN SENGKETA DALAM EKONOMI SYARIAH: TINJAUAN YURIDIS NON LITIGASI - Enny Ratnawati; Nasrullah; Ahmadi Hasan; Mariani (IAIN Ambon, 2026)
Dispute resolution in the Islamic economy is an important aspect to ensure legal certainty, fairness, and the sustainability of business relationships between parties. Until now, dispute resolution through litigation has often been considered ineffective because it is formalistic, time-consuming, and costly. Therefore, non-litigation dispute resolution mechanisms are a relevant alternative and are in line with sharia principles that emphasize deliberation and peace. This article aims to examine the legal basis and models of non-litigation Islamic economic dispute resolution in Indonesia, including arbitration, negotiation, mediation, conciliation, and expert assessment. The research method used is normative juridical with a regulatory and case study approach. The results of the study show that non-litigation dispute resolution has advantages in terms of time efficiency, cost, and maintaining good relations between parties, although it still faces obstacles in the form of limited human resources and a lack of public awareness. Institutional strengthening and increased legal awareness are among the main factors in optimizing non-litigation Islamic economic dispute resolution in Indonesia. Keywords: dispute, islamic economics, non-litigation, legal awareness